Dampak Moderasi Profitabilitas Terhadap Pengaruh CSR, GCG dan Intelectual Capital Terhadap Nilai Perusahaan - Putri Ayunisari; Aristha Purwanthari Sawitri (INVENTORY: JURNAL AKUNTANSI, 2021)
The meaning of the research to understand the impact of CSR, GCG using institutional ownership and IC on value company using PBV with profitability using ROE as moderation. Obtained 14 company samples during the six years of research using a way to take samples by purposive sampling method. The analytical method uses multiple regression analysis and moderated regression analysis provided with SPSS software for Windows 25.00. The results of the partial study showed there was no influence of CSR variables on PBV, GCG variables using institutional ownership showed a positive relati’onship with PBV, IC variables showed no influence on PBV, ROE variables with CSR could not moderate towards PBV, ROE variables with GCG were significantly different PBV which means ROE is a moderating variable that succeeds in agreeing between GCG against PBV, and the ROE and IC interaction variable is not able to moderate against PBV